Extracellular Vesicles in Periodontitis: Pathogenic Mechanisms and Therapeutic Potential - Zhang L; Li X; Zhang B; Li R (Journal of Inflammation Research)
Ling Zhang,1,* Xiaotong Li,2,* Bin Zhang,3 Ruiji Li4 1School of Nursing, Jining Medical University, Jining, Shandong, 272067, People’s Republic of China; 2Department of Stomatology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, 250021, People’s Republic of China; 3Department of Laboratory Medicine, Affiliated Hospital of Jining Medical University, Jining Medical University, Jining, Shandong, 272001, People’s Republic of China; 4School of Pharmacy, Jining Medical University, Rizhao, Shandong, 276826, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruiji Li, School of Pharmacy, Jining Medical University, Xueyuan Road 669, Rizhao, Shandong, 276826, People’s Republic of China, Tel +86-15762380824, Email li-ruiji@mail.jnmc.edu.cnAbstract: Periodontitis is a prevalent yet frequently overlooked oral disease that is linked to a range of systemic conditions. Although basic treatment and periodontal surgery can alleviate the symptoms of periodontitis to a certain extent, the treatment of severe tissue defects or refractory cases is not effective. Extracellular vesicles (EVs) are subcellular lipid bilayer particles that come from a variety of sources and are prevalent in the biological fluids of vertebrates. They play a key role in intercellular communication by transporting multiple signaling molecules. Recent research has indicated that EVs derived from periodontal pathogens can trigger periodontitis, exacerbate the periodontal damage, and potentially disseminate to other parts of the body, leading to systemic conditions. Conversely, extracellular vesicles derived from dental stem cells (DSCs) have demonstrated the ability to regulate the local periodontal immune environment and foster the regeneration and repair of periodontal tissues, positioning them as a promising candidate for cell-free therapeutic approaches to periodontitis. This review aims to summarize the latest research on the involvement of EVs from different sources in the pathogenesis and treatment of periodontitis, especially to systematically elucidate the mechanism of EVs secreted by periodontal pathogens in periodontitis-related systemic diseases for the first time. By uncovering these complex regulatory processes, new and more effective therapeutic approaches can be explored in the battle against periodontitis and its associated systemic diseases. Keywords: extracellular vesicles, outer membrane vesicles, dental stem cells, periodontitis, pathogenesis, therapy